Enhancing Fourth-Grade Mathematical Problem-Solving abilities and Learning Motivation Through Creative Problem Solving with Grobogan Ethnomathematics - Januarti, Audia; Kusuma, Dani (Papanda Publisher, 2025)
Mathematics education faces persistent challenges in engaging elementary students and developing essential problem-solving skills. This study investigated the effectiveness of Creative Problem Solving (CPS) methodology integrated with Grobogan ethnomathematics in enhancing fourth-grade students' mathematical problem-solving abilities and learning motivation. A quasi-experimental design with nonequivalent control groups was employed at SD Negeri 1 Penadaran, Grobogan Regency. The experimental group (n=27) received CPS instruction incorporating Joglo house architectural elements, while the control group (n=16) received conventional instruction. Data were collected through pre-post mathematical problem-solving tests and learning motivation questionnaires. Statistical analyses included one-sample t-tests, binomial proportion tests, independent sample t-tests, and linear regression. The experimental group achieved 93% individual mastery rates and 90% classical achievement levels, significantly exceeding the 70% threshold (p < 0.001). Post-test comparisons revealed significant differences between groups (p = 0.007), with the experimental group demonstrating superior performance. Linear regression analysis showed a strong positive correlation between learning motivation and problem-solving ability (R² = 0.696, r = 0.834), indicating that motivation explained 69.6% of the variance in mathematical performance. The integration of CPS with ethnomathematical elements provided culturally relevant scaffolding that enhanced both cognitive and affective learning outcomes. The Joglo architectural contexts transformed abstract geometric concepts into meaningful, culturally grounded experiences. These findings contribute to culturally responsive pedagogy literature while demonstrating the practical viability of ethnomathematical approaches in elementary mathematics education.